STRATEGI PENINGKATAN PENJUALAN PADA WARUNG SARAPAN PAGI LALA JL. KATIO PEKANBARU - Firmansyah, Firmansyah; Chandra, Roni; Andry, Andry (GERAKAN EDUKASI DAN MASYARAKAT NUSANTARA, 2025)
The results of interviews conducted by the community service team with partners still found existing problems such as the increasing number of competitors selling the same type of breakfast, the lack of partners in promoting breakfast sales, the expected promotions such as the use of digitalization platforms. Responding to existing challenges, the community service team has prepared a work plan or existing solutions based on priorities, namely Providing training and mentoring to partners so that they can utilize sales strategies with platform concepts such as digital to promote products online and expand sales reach, and providing training and mentoring to partners so that they can build an appropriate and attractive brand image so that it is easy for consumers to remember. The method used in this community service activity was a lecture to explain how to increase sales using various existing strategies, based on daily business sales reports. Through a question-and-answer session between the community service team and business owners, the discussion deepened their understanding of sales strategies through discussion/questions and answers. The speaker also introduced them to strategies used to increase sales, which aim to increase market share and reach a wider consumer base. Conclusions from this community service activity included the successful and smooth implementation of the program, knowledge and application of appropriate sales strategies to increase sales, by providing insights into the use of several digital platforms.